ESTUFAS, TELADOS E SUBSTRATOS NO CRESCIMENTO DE MUDAS DE LAVANDA (Lavandula angustifolia Miller) - SOUZA, Larissa Gabriela Pereira,; VIEIRA, Mariane Tavares,; MARQUES, Ana Leticia Ribeiro,; COSTA, Edilson,; DUARTE, Ítala Layane, (ANAIS DO ENIC, 2023)
-